A case of oral herpes zoster associated with meningoencephalitis and tooth exfoliation by alveolar bone resorption. Issue 1 (January 2015) - Okumura, Kenya; Inui, Madoka; Inoue, Jin; Wakabayashi, Hiroki; Tagawa, Toshiro
Abstract We encountered a patient with herpes zoster that initially developed in the mandibular gingival mucosa and induced concomitant spontaneous tooth exfoliation and meningoencephalitis. The patient was a 72-year-old man was diagnosed with herpes zoster of the region innervated by the third branch of the left trigeminal nerve, and treatment with acyclovir at 750 mg/day, div, was initiated. On the following day, the consciousness became disturbed, and the patient was diagnosed with herpes zoster-associated meningoencephalitis at the neurology department of our hospital. The dose of acyclovir was doubled, and steroid pulse therapy was administered concomitantly. The disturbance of consciousness improved and the enanthema disappeared on the 14th hospital day. But spontaneous exfoliation of the left lower second premolar occurred on the 47th hospital day. Based on the elevated serum VZV IgG level measured during the first examination, elevation of the cerebrospinal fluid VZV IgG level during the course, VZV DNA positivity on PCR, and the clinical course, the disease was considered to be herpes zoster that developed initially in the oral mucosa and became complicated by meningoencephalitis and spontaneous tooth exfoliation.